61 Impact of Dedicated Geriatrician Involvement on National Emergency Laparotomy Audit Standards and Outcomes. (16th September 2019) - Coary, Roisin; Jenkins, Kath; Mitchell, Emma; Pullyblank, Anne; Shipway, David
Abstract: Background: Older patients undergoing emergency laparotomy (EmLap) have high levels of mortality and morbidity. The National Emergency Laparotomy Audit (NELA) in the United Kingdom records processes and outcome measures for patients undergoing EmLap. Recent data shows that geriatrician review is associated with reduced post-surgical mortality (Oliver C.M. et al., British Journal of Anaesthesia 2018). Geriatrician review of all patients aged ≥70 years is a NELA standard. However, the most recent national report shows only 23% compliance, falling short of the target of 80% and consistently the poorest performing standard. Methods: In August 2018, we established a dedicated gastrointestinal surgery liaison service to replace ad hoc geriatrician reviews. We evaluated the impact on NELA standard compliance and patient outcomes. Data were extracted from the local NELA database on all patients aged ≥70 years, for the first six months of the service (September to February). These were compared to the same time period in the preceding year prior to service launch. Results: Following service introduction, increased numbers of patients aged ≥70 years underwent EmLap: 50 (2018-9) vs 31 (2017-8). Geriatrician review occurred in 86% (n=43) in 2018-9, compared to 16% (n=5) in 2017-8. Inpatient mortality fell from 23% (n=7) in 2017-8 to 14% (n=7) in 2018-9. Discharge to own home rose to 76% (n=38) in 2018-9 from 68% (n=21) in 2017-8. One patient in each cohort was newly discharged to a nursing home. Mean length of stay was 17.9 days in 2018-9 (range 3-75), versus 17.6 in 2017-8 (range 3-94). Conclusion: Introduction of a dedicated geriatric surgical liaison service is associated with increased compliance with NELA standards. Despite more emergency laparotomies being performed on older patients, this was associated with improved mortality and rates of home discharge, consistent with published data. Targeted investment in surgical liaison services may therefore be warranted.